Immunological Cross Reactions of Antigens of Erysipelothrix Rhusiopathiae and Heart Tissue From Swine - Bratberg, Anna Marie (Acta Vet Scand, 1981)
Antisera against 4 strains of E. rhusiopathiae and against heart tissues from swine were raised in rabbits and used in gel double diffusion precipitation tests against 10 strains of E. rhusiopathiae of various origins and against heart tissues. Precipitation lines showing cross reactions were found in tests with one bacterial antiserum and with both tissue antisera tested. This indicates a similarity between the antigenic determinants of heart muscle and valves from swine and certain strains of E. rhusiopathiae. The possible relationship between the results and the virulence of the microorganisms is discussed.